Medicinal plants with teratogenic potential: current considerations (Brazilian Journal of Pharmaceutical Sciences, 2012)
The aim of this study was to present the implications of the use of herbs during pregnancy, pointing out those that should be avoided during this condition because of their abortifacient and/or teratogenic potential. We carried out searches in the databases ScienceDirect, Scielo and Google Scholar, adopting as criteria for inclusion: book chapters and/or complete articles (with abstract), available in English, Portuguese or Spanish, published from 1996 to in 2011. After a pre-selection of 83 articles, 49 bibliographies were used in the manufacturing end of the article, where 25 were from the Scielo database, 18 from ScienceDirect and 6 from Google Scholar. From the articles studied, we identified the four most commonly used plants as emmenagogue/abortifacient agents by patients of the Department of Prenatal SUS: senne, arruda, boldo and buchinha-do-norte or cabacinha. Thus, we conclude that people often adhere to the maxim "if it's natural, it does no harm" in their rational use of natural products, without the right guidance, believing that these products are safe to use. This usage is even more worrisome among the elderly, pregnant women and children. Regarding the safety of these products, some information and reliable data are scarce or contradictory.